Ecological geography of the sea - Longhurst, Alan R. (Academic Press, 2007)
This book presents an in-depth discussion of the biological and ecological geography of the oceans. It synthesizes locally restricted studies of the ocean to generate a global geography of the vast marine world. Based on patterns of algal ecology, the book divides the ocean into four primary compartments, which are then subdivided into secondary compartments. *Includes color insert of the latest in satellite imagery showing the world's oceans, their similarities and differences *Revised and updated to reflect the latest in oceanographic research *Ideal for anyone interested in understanding ocean ecology -- accessible and informative.